Text-fig. 13. a, d–g: Acer aemilianum. b, c: Acer palmatum and A. sieboldianum modern leaves (NMNS Cleared Leaf Database). a: Oriolo MSF 661, 7-lobed leaf. b: Specimen U 1049, lobe detail showing finely serrate leaf margin. c: Specimen T 0246, 9-lobed leaf with coarsely serrate leaf margin. d: Oriolo MSF 645-1, 9-lobed leaf with two small additional lobes. e: Oriolo MSF 645. f: Oriolo MSF 660, 9-lobed specimen. g: Oriolo MSF 660-1. White arrows indicate position along lamina lobes where marginal serration starts. Scale bars 10 mm (a–c, f, g), 50 mm (d, e). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 13. a, d–g: Acer aemilianum. b, c: Acer palmatum and A. sieboldianum modern leaves (NMNS Cleared Leaf Database). a: Oriolo MSF 661, 7-lobed leaf. b: Specimen U 1049, lobe detail showing finely serrate leaf margin. c: Specimen T 0246, 9-lobed leaf with coarsely serrate leaf margin. d: Oriolo MSF 645-1, 9-lobed leaf with two small additional lobes. e: Oriolo MSF 645. f: Oriolo MSF 660, 9-lobed specimen. g: Oriolo MSF 660-1. White arrows indicate position along lamina lobes where marginal serration starts. Scale bars 10 mm (a–c, f, g), 50 mm (d, e). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 241, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867